Cocoa Farmers’ Preference and Willingness to Pay for Climate-Smart Extension Services (CES): A Choice Experiment Approach - Emmanuel W. Inkoom; Samuel K. N. Dadzie (SAGE Open)
Governments budget cuts to free agricultural extension services in developing countries have led to advocacy for development and implementation of cost-effective extension services to be partly paid for by beneficiary farmers. Accordingly, understanding farmers’ preferences and willingness to pay is essential for successful implementation of any such cost-sharing extension service schemes; but empirical studies to support cost-sharing extension service schemes in the Ghanaian cocoa sector is hard to find. The study contributes to the knowledge gap by examining key drivers of cocoa farmers’ preferences and willingness to pay for a climate-smart extension service using discrete choice experiment data which was analysed with a mixed logit model. Data was collected from 720 cocoa farmers who were sampled using multistage sampling process. The study finds that farmers have significant preference for the climate-smart extension service, with a marginal willingness to pay of approximately GH¢ 15.15 for improvements in product attributes. Farmers’ preferred product attributes include in-person accessibility, advanced climate-smart content, flexible demand-based delivery and high service reliability, taking into consideration price affordability. Additionally, willingness to pay is significantly influenced by perceived service quality, rainfall and temperature variability, climate change impact, age, education, access to credit, and farm income. The study recommends that extension service providers and policymakers should focus on the identified climate-smart cocoa extension service attributes preferred by farmers and the significant determinants of the farmers’ willingness to pay when developing and implementing climate-smart extension services to enhance cocoa farmers’ resilience to climate risks.